2012
DOI: 10.1089/neu.2011.1922
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Nuclear Factor E2-Related Factor 2/Antioxidant Response Element Pathway Is Neuroprotective after Spinal Cord Injury

Abstract: The activation of oxidative damage, neuroinflammation, and mitochondrial dysfunction has been implicated in secondary pathomechanisms following spinal cord injury (SCI). These pathophysiological processes lead to cell death and are tightly regulated by nuclear factor E2-related factor 2/antioxidant response element (Nrf2/ARE) signaling. Here, we investigated whether activation of Nrf2/ARE is neuroprotective following SCI. Female Fischer rats were subjected to mild thoracic SCI (T8) using the New York Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 42 publications
5
58
1
1
Order By: Relevance
“…While our work was in progress, two sets of researchers reported that SF treatment of rodents subjected to SCI leads to improvements in functional and anatomical recovery. 24,25 These studies are in full agreement with our findings that SF treatment after SCI improves hindlimb behavioral outcomes. Furthermore, increases in serotonergic axons caudal to the lesion site in injured SF-treated rats suggest a further protective role for SF administration after SCI.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…While our work was in progress, two sets of researchers reported that SF treatment of rodents subjected to SCI leads to improvements in functional and anatomical recovery. 24,25 These studies are in full agreement with our findings that SF treatment after SCI improves hindlimb behavioral outcomes. Furthermore, increases in serotonergic axons caudal to the lesion site in injured SF-treated rats suggest a further protective role for SF administration after SCI.…”
supporting
confidence: 90%
“…25,38 These independent studies were conducted in a mouse model of compression SCI, in which SF (5 mg/kg IP) was administered 1 h after injury, 38 and in a rat model of contusion SCI, in which SF (5 mg/kg IP) was administered 15 min after injury and once daily for 3 days thereafter. 25 Treatment with SF reduced NFjB pathway activation and decreased levels of cytokine gene expression and protein levels of MMP-9, TNF-a, IL-6, and IL-1b in the spinal cord lesions at 12 and 24 h after SCI. 25,38,39 We detected anti-inflammatory effects at earlier time points using a higher SF dose, with decreased mRNA levels of MMP-9 in the spinal cord seen at 4 h after injury.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, SFN reduced the levels of phosphorylated tau and increased Beclin-1 and LC3-II, suggesting that NRF2 activation might facilitate degradation of this toxic protein through autophagy in the brain (Jo et al, 2014). SFN-treated rats subjected to spinal cord injury had significantly decreased levels of inflammatory cytokines, reduced contusion volume, and improved coordination (Wang et al, 2012). This drug also ameliorated EAE by preserving the blood-brain barrier and by reducing pathologic ROS formation and the number of inflammatory cells .…”
Section: A Electrophilic Nuclear Factor (Erythroid-derived 2)-like 2supporting
confidence: 69%
“…Moreover, we found that HBO-PC induced a significant enhancement of Nrf2 expression in astrocytes of the spinal cord by means of double-immunofluorescence staining with a conventional wide-field fluorescence microscope rather than a confocal fluorescence microscopy. Compared with the previous study, 30 we did not provide the position of Nrf2. So we further investigated the Nrf2 DNA-binding activity and downstream gene expression in the spinal cord with HBO-PC, that indirectly verified the significant enhancement of Nrf2 transcriptional activity.…”
Section: Discussionmentioning
confidence: 97%
“…Because spinal cord injury induces oxidative stress that contributes to progression of secondary injury pathomechanisms, activation of the Nrf2/ARE pathway may reduce oxidative stress leading to neuroprotection. 30 Many studies elegantly highlight the importance of astrocytic Nrf2 for neuronal protection against bioenergetic and oxidative The mRNA levels of glutamate-cysteine ligase (GCL), c-glutamyltransferase (cGT), and multidrug resistance protein 1 (MRP1) in astrocytes measured by real-time polymerase chain reaction were all significantly enhanced at 24 h after HBO-PC (**p < 0.01 vs. CON group), but there is no change in neurons. (B) Using the housekeeping gene b-actin as an internal standard, the protein levels of GCL, cGT, and MRP1 measured by Western blot were significantly increased in astrocytes at 24 h after HBO-PC (**p < 0.01 vs. CON group), but there is no change in neurons.…”
Section: Discussionmentioning
confidence: 99%